OBLIGATORIEDAD DEL SEGURO AMBIENTAL EN LA LEY DE GESTIÓN AMBIENTAL - IÑAHUAZO CULQUICONDOR, EDGAR ALBERTO (2016)
Environment constitute source of natural elements, values social and cultural to exist a clear relationship, faces serious environmental problems and development generated by factors such as the exploitation of natural resources and the lack of proper and timely implementation of the principles of prevention and precaution, that are the basis of sustainability and environmental recoverycurrently common is obvious and costly environmental damage, in response a tolerant attitude to these situations violate the environment; in order to mitigate these environmental damage and as a measure of prevention, precaution and in addition to restoration, there is a suitable instrument called a compulsory environmental insurance, not with the purpose of hold harmless, or to protect the heritage of the contractor of insurance but friendly; insurance is a useful tool of prevention of damage since the value of the premium, as well as the insurable amount will be directly related to the environmental management of the activity in prevention, on the basis of the risk assessment to be performed; Environmental management of our country act regulates non-obligatory risk insurance because they are just instruments of implementation of environmental standards, so that the use of the mechanisms of assurance are aimed at certain specific activities are precise and clearly identify the areas of coverage of the policies against a constitutional legislation that recognizes the right of the population to live in a healthy and ecologically balanced environment, to ensure sustainability and good living, sumak kawsay which also declares public interest the preservation of the environment, the conservation of ecosystems, biodiversity and the integrity of heritage genetic of the country, the prevention of environmental damage and recovery of degraded natural areas (Art.14); in which the State reserves the right to manage, regulate, control and manage the strategic sectors, in accordance with the principles of environmental sustainability, precaution, prevention and efficiency (Art.313); and in order to guarantee the individual and collective right to live in an environment healthy and ecologically balanced, the State undertakes to: Establishing effective mechanisms for the prevention and control of environmental pollution, recovery of degraded natural areas and sustainable management of natural resources (Art. 397, 2), in such a way the importance of new tools in order to ensure the protection of the environment is based on the corresponding constitutional rules that introduce compulsory environmental insurance in legally correct way through regulations that set out clearlyIt is an important element to give effect to these principles and constitutional rights in favour of the environment and nature, it is so undoubtedly the compulsory environmental insurance is a mechanism of prevention and precaution to mitigate environmental damage and also constitutes a tool for restoration of ecosystems; Another aspect to highlight is the fact that regulate properly the compulsory environmental insurance in Ecuadorian legislation implies the fulfilment of the right of the population to live in a healthy and ecologically balanced environment guaranteeing sustainability and good living, sumak kawsay; and finally to ensure the compensation of third parties affected are these communities in isolation, populations that depend on and affect directly the offensive actions against nature.